Preparation method of nano-catalyst for reduction reaction of p-nitrophenol
By preparing the nanocatalyst Au/CoMoS2, the CoMoS2 sample was synthesized by hydrothermal method and the Au nanoparticles were anchored, the problem of excessive treatment of 4-nitrophenol in the prior art was solved, and efficient catalytic reduction effect was achieved.
Patent Information
- Application Number
- CN202411691721.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The method used in the prior art for treating 4-nitrophenol has a problem that the treatment time is too long.
By preparing the nanocatalyst Au/CoMoS2, the CoMoS2 sample was synthesized by hydrothermal method, and the Au nanoparticles were anchored on the support by NaBH4 reduction to form the Au/CoMoS2 catalyst.
Au/CoMoS2 catalysts exhibit excellent catalytic activity, especially when the molar ratio of Co to Mo is 2:8, the apparent rate constant (kapp) of catalytic 4-NP reduction to 4-AP can reach 1.063, significantly shortening the reaction time.
Smart Images

Figure CN119524884A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst preparation, in particular to a method for preparing a nano catalyst for a p-nitrophenol reduction reaction. Background Art
[0002] Nitrophenol compounds are one of the main sources of water pollution due to their high toxicity, good water solubility and stability. Especially 4-nitrophenol (4-NP), as a major pollutant in the pharmaceutical and dye industries, it is particularly urgent to find a method to control and treat it. And in the prior art, there are multiple methods for treating 4-NP, specifically including adsorption, biodegradation, electrochemical removal and chemical reduction. But in actual use, it is found that these methods have the problem of long processing time. Summary of the invention
[0003] In view of the technical problem that the processing time in the prior art method is too long, the present invention provides a method for preparing a nano catalyst for the reduction reaction of p-nitrophenol.
[0004] The technical solution adopted by the present invention is: a method for preparing a nanocatalyst for the reduction reaction of p-nitrophenol, which specifically comprises the following steps:
[0005] Preparation of S1, MoS2:
[0006] S101, adding 1 mmol of ammonium heptamolybdate and 30 mmol of thiourea into 40 mL of deionized water, and stirring the mixture magnetically for 30 minutes;
[0007] S102, pouring the stirred transparent solution into a stainless steel polytetrafluoroethylene-lined autoclave and heating it at 200° C. for 12 hours;
[0008] S103, the obtained sample was centrifuged and washed with pure water and ethanol, and dried at 80 °C for 8 hours to obtain MoS2;
[0009] S2, CoMoS2 preparation:
[0010] S201, adding 1 mmol of a mixture containing ammonium heptamolybdate and cobalt chloride hexahydrate and 30 mmol of thiourea to 40 mL of deionized water, and performing magnetic stirring for 30 minutes;
[0011] S202, pouring the stirred transparent solution into a stainless steel polytetrafluoroethylene-lined autoclave and heating it at 200°C for 12 hours;
[0012] S203, the obtained sample was centrifuged and washed with pure water and ethanol, and dried at 80°C for 8 hours to obtain CoMoS2;
[0013] Preparation of S3, Au / MoS2 and Au / CoMoS2 catalysts:
[0014] S301, anchoring Au nanoparticles on the support by NaBH4 reduction:
[0015] The details are as follows: 40 mg of MoS2 or CoMoS2 is ultrasonically dispersed into 20 mL of a mixed solution of water and ethanol, wherein the volume ratio of water to ethanol is 18:2, 5.17 mL of HAuCl4 solution with a molar concentration of 0.01 mol / L is added to the above mixed solution, and magnetic stirring is performed for 24 hours, 30 mg of NaBH4 is added to the above mixture and magnetic stirring is performed for 1 hour, and finally the product is separated, washed with pure water and ethanol and dried at 80°C for 8 hours to obtain Au / MoS2 and Au / CoMoS2 nanocomposites.
[0016] The present invention is further configured such that, in step S3, M Co :M Mo The molecular ratio ranges from 1:9 to 4:6.
[0017] The present invention is further configured to further include a catalytic reaction experiment, the specific steps of which are as follows:
[0018] 3 mL of 4-NP solution (0.1 mmol / L) was added to a quartz cuvette, and 0.15 mL of NaBH4 solution (0.1 mol / L) was added. After thorough mixing, 1 mg of Au / MoS2 or Au / CoMoS2 catalyst was added to start the catalytic reduction reaction. The progress of the reduction reaction was monitored by monitoring the UV-visible absorption spectrum (400 nm) of 4-NP at different reaction times.
[0019] The present invention is further configured to further include testing the crystal structure of the catalyst using an X-ray diffractometer under Cu radiation of 40 kV and 30 mA, and the specific steps are as follows:
[0020] First, the XRD spectra of different samples were measured by scanning in the angle range of 5–90° (2θ) at a speed of 5° / min;
[0021] Secondly, the morphology was characterized on a field emission scanning electron microscope to obtain SEM images to observe the catalyst morphology, and the element spectrum was analyzed by an energy dispersive X-ray (EDX) element analysis system.
[0022] Again, transmission electron microscopy (TEM) images were obtained by a Tecnai G220 TWIN microscope operated at 200 kV;
[0023] Subsequently, Raman spectra were measured on a Renishaw Raman microspectrometer;
[0024] Finally, X-ray photoelectron spectroscopy was performed on a ThermoFischer ESCALAB Xi+ using an Al K monochromatic source to obtain elemental information.
[0025] The beneficial effects of the present invention are as follows: in the present invention, a series of CoMoS2 samples with different Co and Mo molar ratios are prepared by introducing Co as a heteroatom, and used to anchor gold nanoparticles, and the synthesized Au / CoMoS2 catalyst exhibits excellent catalytic activity, especially when the molar ratio of Co to Mo is 2:8, the Au / CoMoS2 (M Co :M Mo =2:8) showed the best catalytic performance, and its apparent rate constant (k app ) can reach 1.063. The experiment uses a series of characterization methods such as XRD, SEM, TEM, Raman spectroscopy, XPS, etc. to analyze the physicochemical properties of the catalyst in detail, and on this basis, discusses the promoting effect of cobalt on the catalytic reduction of 4-NP by Au / CoMoS2 catalyst. In summary, the present invention synthesizes cobalt-modified MoS2 by a simple hydrothermal method as a perfect carrier of Au nanoparticles to prepare a catalytic system with enhanced activity for the 4-NP reduction reaction, and the reaction treatment time is short. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Schematic diagram of the preparation process of CoMoS2 and Au / CoMoS2, and the catalytic application of 4-NP reduction to 4-AP;
[0027] Figure 2a -f is the UV-visible absorption spectra of NaBH4-catalyzed reduction of p-NP (ae) and ln(C t / C0) versus reaction time (t) (f);
[0028] Figure 3a -b is a series of X-ray diffraction patterns of CoMoS2 (a) and Au / CoMoS2 (b);
[0029] Figure 4a -b is the Raman spectra of Au / MoS2 and Au / CoMoS2, where the molar ratio of Co / Mo varies from 1:9 to 4:6;
[0030] Figure 5a -b is the UV-visible absorption spectra of MoS2 and Au / MoS2 (a); UV-visible absorption spectra of CoMoS2 (2 / 8) and Au / CoMoS2 (2 / 8) (b);
[0031] Figure 6a-k are the morphological diagrams of the synthesized samples: SEM images of MoS2 (a), Au / MoS2 (b), CoMoS2 (2 / 8) (c) and Au / CoMoS2 (2 / 8) (d); TEM images of MoS2 (e), Au / MoS2 (f), CoMoS2 (2 / 8) (h) and Au / CoMoS2 (2 / 8) (i); size distribution of Au nanoparticles of Au / MoS2 (g) and Au / CoMoS2 (2 / 8) (j); SEM spectrum of Au / CoMoS2 (2 / 8) (k);
[0032] Figure 7a -c are XPS spectra of Au / MoS2 and Au / CoMoS2(2 / 8), respectively: (a) Au 4f; (b) Mo 3d; (c) S2P. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] refer to Figure 1 -7, in order to solve the problems existing in the background technology, the present application proposes the following technical solution: a method for preparing a nanocatalyst for the reduction reaction of p-nitrophenol, specifically comprising the following steps:
[0035] Preparation of S1, MoS2 (synthesized by hydrothermal method):
[0036] S101, adding 1 mmol of ammonium heptamolybdate and 30 mmol of thiourea into 40 mL of deionized water, and stirring the mixture magnetically for 30 minutes;
[0037] S102, pouring the stirred transparent solution into a stainless steel polytetrafluoroethylene-lined autoclave and heating it at 200° C. for 12 hours;
[0038] S103, the obtained sample was centrifuged and washed with pure water and ethanol, and dried at 80 °C for 8 hours to obtain MoS2;
[0039] S2, CoMoS2 preparation (synthesized by hydrothermal method):
[0040] S201, adding 1 mmol of a mixture containing ammonium heptamolybdate and cobalt chloride hexahydrate and 30 mmol of thiourea to 40 mL of deionized water, and performing magnetic stirring for 30 minutes;
[0041] S202, pouring the stirred transparent solution into a stainless steel polytetrafluoroethylene-lined autoclave and heating it at 200°C for 12 hours;
[0042] S203, the obtained sample was centrifuged and washed with pure water and ethanol, and dried at 80°C for 8 hours to obtain CoMoS2;
[0043] Preparation of S3, Au / MoS2 and Au / CoMoS2 catalysts:
[0044] S301, anchoring Au nanoparticles on the support by NaBH4 reduction:
[0045] Specifically, 40 mg of MoS2 or CoMoS2 was ultrasonically dispersed in a mixed solution of 20 mL of water and ethanol, wherein the volume ratio of water to ethanol was 18:2, 5.17 mL of HAuCl4 solution with a molar concentration of 0.01 mol / L was added to the mixed solution, and magnetic stirring was performed for 24 h, 30 mg of NaBH4 was added to the mixture and magnetic stirring was performed for 1 h, and finally the product was separated, washed with pure water and ethanol, and dried at 80 ° C for 8 h to obtain Au / MoS2 and Au / CoMoS2 nanocomposites;
[0046] The products used in the present invention are as follows: ethanol (C2H5OH), chloroauric acid (HAuCl4·4H2O), sodium borohydride (NaBH4) and cobalt chloride hexahydrate (CoCl2·6H2O) were purchased from Aladdin Industrial Co., Ltd. (Shanghai, China). 4-Nitrophenol (C6H5NO3), ammonium molybdate tetrahydrate ((NH4)6Mo7O 24 ·4H2O) and thiourea (CH4N2S) were purchased from Merck (Darmstadt, Germany).
[0047] In step S3, M Co :M Mo The molecular ratio ranges from 1:9 to 4:6.
[0048] Experimental example
[0049] Experimental Example 1 also includes a catalytic reaction experiment (ultraviolet-visible spectroscopy), and the specific steps are as follows:
[0050] 3 mL of 4-NP solution (0.1 mmol / L) was added to a quartz cuvette, followed by 0.15 mL of NaBH4 solution (0.1 mol / L). After thorough mixing, 1 mg of Au / MoS2 or Au / CoMoS2 catalyst was added to start the catalytic reduction reaction. The progress of the reduction reaction was monitored by monitoring the UV-visible absorption spectrum (400 nm) of 4-NP at different reaction times.
[0051] Experimental Example 2:
[0052] The crystal structure of the catalyst was also tested using an X-ray diffractometer (XRD 6000, Shimadzu, Japan) under Cu radiation at 40 kV and 30 mA. The specific steps are as follows:
[0053] First, the XRD spectra of different samples were measured by scanning in the angle range of 5–90° (2θ) at a speed of 5° / min;
[0054] Secondly, the morphological characterization was carried out on a field emission scanning electron microscope (FE-SEM) (model SU8010, Hitachi, Japan) to observe the catalyst morphology, and the elemental spectrum was analyzed by the equipped energy dispersive X-ray (EDX) elemental analysis system;
[0055] Again, transmission electron microscopy (TEM) images were obtained by a Tecnai G220 TWIN microscope operated at 200 kV;
[0056] Subsequently, the Raman spectra were measured on a Renishaw Raman microspectrometer (model invia, UK);
[0057] Finally, X-ray photoelectron spectroscopy was performed on a ThermoFischer ESCALAB Xi+ using an Al K monochromatic light source (hv = 1486.6 eV) to obtain elemental information.
[0058] Experimental example analysis:
[0059] Testing of the catalytic performance of 4-NP reduction:
[0060] The catalytic effect of the synthesized catalyst on the reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP) was evaluated by UV-visible spectroscopy. 4-NP showed a characteristic absorption peak at 320 nm. With the addition of NaBH4, the absorption peak shifted to 400 nm to form p-nitrophenol ions. In the control group without the addition of the catalyst, the peak at 320 nm did not change after a considerable period of time.
[0061] After adding the catalyst, refer to Figure 2a-2e As shown, the peak of 4-AP at 400nm gradually decays, while the peak of 4-AP at 300nm gradually increases. For different catalysts, the decay rate of the peak at 400nm is different. Among them, Au / MoS2 has the lowest catalytic activity. After adding cobalt to the catalyst, the activity of various Au / CoMoS2 catalysts has been improved to a certain extent. Au / CoMoS2 (2 / 8) with a Co / Mo molar ratio of 2 / 8 shows the highest activity, which can complete the conversion of 4-NP to 4-AP within 4 minutes.
[0062] By plotting ln(C t The relationship between C0 and C t are the 4-NP concentrations at the initial moment and at t minutes, respectively. Figure 2f As shown in the figure, the apparent rate constant (k app ) is calculated based on the slope of the fitting curve, and the data are listed in Table 1;
[0063] k of Au / CoMoS2(2 / 8) app 1.063min -1 , Table 2 lists the comparison of Au / CoMoS2(2 / 8) with some other Au-based catalysts reported in the literature. The results show that the synthesized Au / CoMoS2(2 / 8) catalyst exhibits excellent performance in 4-NP reduction;
[0064] catalyst <![CDATA[K app (min -1 )]]> <![CDATA[Au / MoS2]]> 0.083 <![CDATA[Au / CoMoS2(1 / 9)]]> 0.234 <![CDATA[Au / CoMoS2(2 / 8)]]> 1.063 <![CDATA[Au / CoMoS2(3 / 7)]]> 0.426 <![CDATA[Au / CoMoS2(4 / 6)]]> 0.235
[0065] Table 1: Apparent rate constants (k app ).
[0066]
[0067]
[0068] Table 2: Comparison of catalyst Au / CoMoS2 (2 / 8) with other catalysts.
[0069] Among them, Figure 3 shows the XRD patterns (X-ray diffraction patterns) of MoS2 and a series of Au / CoMoS2 samples. Figure 3a It can be observed that MoS2 shows XRD peaks at 14.3°, 33.7°, 40.1°, and 59.2°, corresponding to the (002), (100), (103), and (110) crystal planes, respectively, which include the characteristic peaks of 1T-MoS2 (2θ=33.7°) and 2H-MoS2 (2θ=40.1o);
[0070] Therefore, the synthesized MoS2 contains both 1T and 2H phases. For a series of CoMoS2 samples with different Co / Mo ratios, the diffraction peaks are almost the same as those of MoS2, and no new diffraction peaks are shown after the addition of cobalt, which means that the CoMoS2 carrier maintains the crystal structure of MoS2, and cobalt is more evenly dispersed in the prepared catalyst or the cobalt particles are relatively small;
[0071] like Figure 3bAs shown in the figure, after Au was loaded on a series of samples, some new peaks appeared at 38.5°, 44.6°, 64.8°, 77.9° and 82.1°. The appearance of these peaks was attributed to the diffraction effect of Au nanoparticles, corresponding to the (110), (200), (220), (311) and (222) crystal planes, respectively, which indicated that Au was successfully loaded on MoS2 and CoMoS2.
[0072] Among them, in the prior art, Raman spectroscopy has been used to characterize the interface quality of MoS2, which is affected by strain, defects and dislocations; Figure 4a As shown, two Raman bands of MoS2 were observed, located at 379.7 cm -1 404.8cm -1 They are respectively attributed to the in-plane E 1 2g Mode and out-of-plane A 1g Mode; E 1 2g The mode originates from the opposite vibrations of two S atoms relative to the Mo atoms in the basal plane. 1g The modes originate from the out-of-plane vibrations of the Mo-S bonds;
[0073] from Figure 4a It can be observed that the E of CoMoS2(2 / 8) 1 2g The mode shifted 1.1cm to the lower angle -1 , which may be caused by the dislocation or defects of Mo and S atoms, which also causes more active edge sites to be exposed and improves the catalytic activity; the spectrum of Au / CoMoS2(2 / 8) shows a rather broad and weak E 1 2g band, which indicates the presence of crystal defects in the basal plane. The typical E 1 2g and A 1g The spectral bands were blue-shifted to 381.1 cm -1 and 407.3cm -1 , which reveals the effect of metal doping on MoS2;
[0074] Although Au / MoS2 does not blue-shift but red-shifts after Au loading, this difference may be due to the effect of adding cobalt on the structure and composition of MoS2. Figure 4b A series of Au / MoS2(1 / 9-4 / 6), E 1 2g and A 1g The peak of E is basically the same as that of Au / CoMoS2(2 / 8). 12g and A 1g The distance between them is a signal of the number of MoS2 layers. The distance will increase with the increase of MoS2 layers. The distance between a series of Au / CoMoS2 samples and Au / MoS2 is 25.6 cm -1 and 24.1cm -1 , these values are consistent with those reported for the three-layer structure.
[0075] Among them, the UV-Vis spectra of MoS2, Co-doped CoMoS2 (2 / 8), and Au-loaded samples are shown in Figure 5;
[0076] MoS2 and CoMoS2 (2 / 8) at 550nm -1 There is an adsorption peak near the surface of Au nanoparticles, and after Au nanoparticles loading, the peak red-shifted to 590 nm. -1 This indicates that the band gap of MoS2 is narrowed. This phenomenon reveals that there is a strong metal-support interaction between Au and the support. During the catalytic reduction of 4-NP, the reaction involves the adsorption of 4-NP and borohydride on the catalyst surface, as well as the electron transfer between the catalyst and the reactants or reaction products. The narrowing of the support's band gap helps electron transport, thereby further promoting the catalytic reaction.
[0077] Among them, it can be seen from the SEM images shown in Figure 6 (ad) that both the synthesized MoS2 and the cobalt-doped MoS2 exhibit nanosheet structures with abundant edges, and the nanosheets aggregate to form flower-like nanoclusters with a diameter of about 1 μm, and it can be concluded that the loading of Au nanoparticles on the sample does have a significant effect on the sample morphology;
[0078] The nanosheet structures of MoS2 and CoMoS2 can be further confirmed by TEM images (Figure 6 (e, h)). After loading Au nanoparticles on these carriers, as shown in Figure 6 (f, i), it can be observed that the Au nanoparticles are uniformly dispersed on the nanosheets, and the size of the Au nanoparticles is mainly distributed in the range of 5-20 nm;
[0079] Figure 6g and Figure 6h The size distribution of Au nanoparticles was summarized, and the average Au particle sizes of Au / MoS2 and Au / CoMoS2 (2 / 8) were 10.70 nm and 9.15 nm, respectively;
[0080] like Figure 6k In the EDX analysis of Au / CoMoS2(2 / 8) shown, the elemental mapping of Mo, Co, and Au confirmed that Au nanoparticles were successfully and uniformly loaded on the surface, while cobalt was highly dispersed in MoS2, which is consistent with the XRD results.
[0081] Among them, in order to explore the surface valence state of elements, XPS spectroscopy was used to characterize two typical catalysts, Au / MoS2 and Au / CoMoS2; Figure 7a The Au 4f spectra of the two catalysts are shown, where the peak at 84.1 eV corresponds to the (4f 7 / 2 ), while 87.8 eV corresponds to Au's (4f 5 / 2 ), which is similar to the metal gold (Au 0 ), for Au / CoMoS2, its binding energy decreases slightly, about 0.1eV, which may be due to the interaction between Au and Co;
[0082] like Figure 7b In the Mo 3d spectrum shown, the double peaks at 232.4 eV and 229.2 eV correspond to Mo 4+ 3d 3 / 2 and Mo 4+ 3d 5 / 2 Characteristic peaks, these two peaks are Mo 4+ The characteristic peaks of sulfur binding, despite the presence of Mo 4+ There are also double peaks at 235.8eV and 233.3eV, corresponding to Mo 6+ 3d 3 / 2 and Mo 6+ 3d 5 / 2 Characteristic peaks;
[0083] In summary, the appearance of these peaks indicates that MoS2 has been oxidized, which is caused by the reactivity of the synthesized catalyst, especially at the edge sites. 6+ The ratio is higher than that of Au / MoS2, which indicates that Co improves the reactivity of the catalyst by creating more active edge sites, which is consistent with the results of Raman spectroscopy;
[0084] Figure 7c The double peaks of S2p are shown, located at 163.2eV and 162.0eV, which correspond to S2p 1 / 2 and S2p 3 / 2 , indicating the presence of divalent sulfide ions; in addition, the oxidized species of S also appeared at 168.5 eV, which may be the result of partial oxidation of the active surface, more specifically, the oxidation of exposed sulfur atoms at the edge sites.
[0085] It is well known that the S atoms at the edge of the catalyst are the active sites of the catalytic reaction. The sulfur oxide peak area of Au / CoMoS2(2 / 8) is larger than that of Au / MoS2, which indicates that its active sites are more exposed. Adding cobalt can improve the reactivity of the catalyst. In addition, the binding energy of Au 4f, Mo S 3d and S2P of Au / CoMoS2(2 / 8) is lower than that of Au / MoS2, which confirms the influence of the strong electronic interaction between Co, Mo, S and Au on the chemical environment.
[0086] In addition, Table 3 lists the binding energy and peak area data of this series of peaks.
[0087]
[0088] Table 3: XPS data of Au / MoS2 and Au / CoMoS2 (2 / 8);
[0089] In summary, the present invention synthesized cobalt-modified MoS2 via a simple hydrothermal method as a perfect support for Au nanoparticles to prepare a catalytic system with enhanced activity for 4-NP reduction reaction;
[0090] In the present invention, a series of CoMoS2 samples with different Co and Mo molar ratios were prepared by introducing cobalt (Co) as a heteroatom and used to anchor gold nanoparticles. The synthesized Au / CoMoS2 catalysts exhibited excellent catalytic activity, especially when the molar ratio of Co to Mo was 2:8. Co :M Mo =2:8) showed the best catalytic performance, and its apparent rate constant (k app ) can reach 1.063. The physical and chemical properties of the catalyst were analyzed in detail through a series of characterization methods such as XRD, SEM, TEM, Raman spectroscopy, XPS, etc., and on this basis, the promoting effect of cobalt on the catalytic reduction of 4-NP over Au / CoMoS2 catalyst was discussed.
[0091] The optimal addition ratio of Co:Mo (mol) is 2:8, and the synthesized Au / CoMoS2 (2 / 8) exhibits the best activity. The experimental process uses a simple method to obtain high-performance results. The catalytic activity is effectively improved by adding cobalt. This is because the more crystal defects are generated, the more exposed edge active sites are, and the more convenient the electron transfer is, which makes the reactive surface properties better.
[0092] This study further explored cobalt (Co)-modified molybdenum disulfide (MoS2)-loaded gold (Au) nanoparticles (Au / Co-MoS2) as a catalyst for the reduction reaction of 4-NP;
[0093] The experimental results show that the catalytic activity of the catalyst is significantly improved after the introduction of cobalt, especially when the molar ratio of Co to Mo is 2:8, the catalyst exhibits the best catalytic performance. The catalyst characterization results show that the introduction of cobalt increases crystal defects and promotes the exposure of active edge sites, thereby enhancing the catalytic activity of the catalyst surface.
[0094] While the embodiments of the present invention have been shown and described, it will be apparent to those skilled in the art that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a nanocatalyst for the reduction reaction of p-nitrophenol, characterized in that: The specific steps include: Preparation of S1, MoS2: S101, adding 1 mmol of ammonium heptamolybdate and 30 mmol of thiourea into 40 mL of deionized water, and stirring the mixture magnetically for 30 minutes; S102, pouring the stirred transparent solution into a stainless steel polytetrafluoroethylene-lined autoclave and heating it at 200° C. for 12 hours; S103, the obtained sample was centrifuged and washed with pure water and ethanol, and dried at 80 °C for 8 hours to obtain MoS2; S2, CoMoS2 preparation: S201, adding 1 mmol of a mixture containing ammonium heptamolybdate and cobalt chloride hexahydrate and 30 mmol of thiourea to 40 mL of deionized water, and performing magnetic stirring for 30 minutes; S202, pouring the stirred transparent solution into a stainless steel polytetrafluoroethylene-lined autoclave and heating it at 200°C for 12 hours; S203, the obtained sample was centrifuged and washed with pure water and ethanol, and dried at 80°C for 8 hours to obtain CoMoS2; Preparation of S3, Au / MoS2 and Au / CoMoS2 catalysts: S301, anchoring Au nanoparticles on the support by NaBH4 reduction: The details are as follows: 40 mg of MoS2 or CoMoS2 is ultrasonically dispersed into 20 mL of a mixed solution of water and ethanol, wherein the volume ratio of water to ethanol is 18:2, 5.17 mL of HAuCl4 solution with a molar concentration of 0.01 mol / L is added to the above mixed solution, and magnetic stirring is performed for 24 hours, 30 mg of NaBH4 is added to the above mixture and magnetic stirring is performed for 1 hour, and finally the product is separated, washed with pure water and ethanol and dried at 80°C for 8 hours to obtain Au / MoS2 and Au / CoMoS2 nanocomposites.
2. The method for preparing a nanocatalyst for the reduction reaction of p-nitrophenol according to claim 1, characterized in that: In step S1 and step S3, M Co :M Mo The molecular ratio ranges from 1:9 to 4:
6.
3. The method for preparing a nanocatalyst for the reduction reaction of p-nitrophenol according to claim 2, characterized in that: Including catalytic reaction experiments, the specific steps are as follows: 3 mL of 4-NP solution (0.1 mmol / L) was added to a quartz cuvette, and 0.15 mL of NaBH4 solution (0.1 mol / L) was added. After thorough mixing, 1 mg of Au / MoS2 or Au / CoMoS2 catalyst was added to start the catalytic reduction reaction. The progress of the reduction reaction was monitored by monitoring the UV-visible absorption spectrum (400 nm) of 4-NP at different reaction times.
4. The method for preparing a nanocatalyst for the reduction reaction of p-nitrophenol according to claim 3, characterized in that: The crystal structure of the catalyst was also tested using an X-ray diffractometer under Cu radiation at 40 kV and 30 mA. The specific steps are as follows: First, the morphological characterization was carried out on a field emission scanning electron microscope by scanning at a speed of 5o / min in the angle range of 5–90o to observe the catalyst morphology, and the elemental spectrum was analyzed by the equipped energy dispersive X-ray (EDX) elemental analysis system; Secondly, X-ray photoelectron spectroscopy was performed on a ThermoFischer ESCALAB Xi+ using an Al K monochromatic light source to obtain elemental information; Subsequently, Raman spectra were measured on a Renishaw Raman microspectrometer; Finally, transmission electron microscopy (TEM) images were obtained by a Tecnai G220 TWIN microscope operating at 200 kV.